ESTUDO EXPERIMENTAL DA CAPACIDADE DE SORÇÃO E DESORÇÃO DE FENÓIS EM SOLOS DA ÁREA DA ALBRAS - BARCARENA/PA - BRASIL - Pacheco Júnior, A. C.; Souza, E. L.; da Rocha Filho, G. N. (Geochimica Brasiliensis, 2012)